Research Trend on Korean Wave: a Bibliometric Study (2015-2025) - Chaidira, Zalza; Purwaningtyas, Franindya (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study maps trends in Korean Wave-themed scholarly publications from 2015 to 2025 to contribute to academic literature and guide researchers and practitioners in addressing information needs influenced by popular culture. Using a descriptive quantitative approach with bibliometric analysis, data were collected from Google Scholar via Publish or Perish software with the keywords “Korean Wave” AND “Bibliometrics.” Ninety-nine articles were analyzed after cleaning in Microsoft Excel, with visualization conducted in VOSviewer through network, overlay, and density maps. Validation was performed by reviewing 10% of abstracts and checking metadata consistency. The analysis identified six main keyword clusters linking the Korean Wave to consumer behavior, cultural diplomacy, social media, and tourism. Overlay visualizations revealed a thematic shift from descriptive to analytical research, with emerging trends such as “art diplomacy” and “consumer behavior.” Co-authorship analysis showed limited collaboration among authors despite the presence of active research groups. Dominant topics include tourism, drama series, music, and beauty. The findings demonstrate the effectiveness of bibliometric methods in mapping Korean Wave research dynamics within Library and Information Science, providing conceptual insights into thematic development and scholarly networks. Future research is advised to utilize reputable databases like Scopus or Web of Science and incorporate qualitative approaches for a more comprehensive understanding .